Effects on poverty and equity of the decline in collective tank irrigation management in Tamil Nadu, India - Kajisa, Kei; Palanisami, K.; Sakurai, Takeshi (Wiley, 2007)
This paper investigates the factors influencing the decline in collective management of local commons and the impact of this decline on agricultural production and household consumption. The analysis is based on a village and household data set collected in 1999 in Tamil Nadu, India, where tank irrigation systems are managed collectively for rice cultivation by informal water users' organizations. Our statistical analyses find that one major reason for the decline in collective tank irrigation management is the dissemination of private well irrigation systems. Once the decline has occurred, our analyses predict that the gap in rice yields between farmers who have access to private wells and those who must rely solely on tanks will widen, with only the latter group suffering lower yields. Our analyses also find that the same pattern holds for levels of income and consumption because the affected farmers cannot sufficiently compensate for the loss of their rice income by diversifying their income sources to agricultural labor or nonagricultural work. In this way, the decline in collective management results in greater inequality and poverty.